2013
DOI: 10.1002/stem.1377
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Distal Airway Progenitor Cells, Lung Mechanics, and Disproportionate Lobar Growth Following Long-Term Postpneumonectomy in Mice

Abstract: Utilizing a model of post-pneumonectomy (PNY) compensatory lung growth in mice, we previously observed an increase in numbers of a putative endogenous distal airway progenitor cell population (CCSPpos/pro-SPCpos cells located at bronchoalveolar duct junctions (BADJ)), at 3, 7, and 14 days after pneumonectomy, returning to baseline at 28 days post-PNY. As the origin of these cells is poorly understood, we evaluated whether bone marrow cells contributed to the pool of these or other cells during prolonged post-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…New alveolar tissue is preferentially laid down at the periphery of the lung (Foster et al, 2002; Massaro and Massaro, 1993) where mechanical strain of the septa is accentuated due to a relative lack of bronchovascular support (Yilmaz et al, 2011). Evidence exists for proliferation and changes in the behavior of multiple cell lineages in the PNX model, including bronchiolar cells, AEC2s, endothelial cells and Pdgfrα+ stromal cells (Chen et al, 2012b; Eisenhauer et al, 2013; Hoffman et al, 2010; Hsia, 2004; Thane et al, 2014; Voswinckel et al, 2004). …”
Section: Remodeling and Regrowth Of The Alveolar Region After Pneumonmentioning
confidence: 99%
“…New alveolar tissue is preferentially laid down at the periphery of the lung (Foster et al, 2002; Massaro and Massaro, 1993) where mechanical strain of the septa is accentuated due to a relative lack of bronchovascular support (Yilmaz et al, 2011). Evidence exists for proliferation and changes in the behavior of multiple cell lineages in the PNX model, including bronchiolar cells, AEC2s, endothelial cells and Pdgfrα+ stromal cells (Chen et al, 2012b; Eisenhauer et al, 2013; Hoffman et al, 2010; Hsia, 2004; Thane et al, 2014; Voswinckel et al, 2004). …”
Section: Remodeling and Regrowth Of The Alveolar Region After Pneumonmentioning
confidence: 99%
“…This postnatal lung-growth model has been optimized in a variety of species, including rat, mouse and dog 8487 , and was recently demonstrated to occur in a selected human case 88 . Most studies so far have suggested that lung growth after PNX involves rapid, coordinated proliferation of a broad diversity of lung lineages, including most epithelial and endothelial cells, and only a minority of reports suggest that specialized rare stem or progenitor cells, such as putative BASCs, have a specialized or initiating role in the process 85,89,90 . In marked contrast, when a highly selective injury model, such as naphthalene-induced ablation of mature club cells, is used, a rare subset of epithelial cells, variant club cells, that have survived the injury then reconstitute the airway in a process that shows features of classically defined facultative progenitors, including reactivation of proliferation.…”
Section: Are Most Lung Epithelial Cells ‘Stem Cells’?mentioning
confidence: 99%
“…On the other hand, one recent study using a model of postpneumonectomy with compensatory lung growth in mice found that no donor BM-derived cells engrafted as airway or alveolar epithelial cells at the bronchoalveolar duct junction, a site where putative progenitor cells have been found [29]. The use of different lung injury models may be the reason for these divergent results, suggesting that the contribution of BM-derived cells to the endogenous pool of lung progenitor populations may vary with the lung disease, the type of injury and the repair process.…”
Section: Inflammation and Remodelling Of The Airways In Chronic Lumentioning
confidence: 99%